PEMBERDAYAAN MEDITOR LOKAL SEBAGAI PROBLEM SOLVER DALAM SENGKETA PERCERAIAN MASYARAKAT MUSLIM DESA KALISAT PASURUAN - Salam, Nor; Nurcholis, Moch.; Junaidin, Junaidin (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2023)
The activity with the theme “Empowering Local Meditors as Problem Solvers in Divorce Disputes in the Muslim Community of Kalisat Pasuruan Village” was motivated by the presence of a Supreme Court Regulation (PERMA) with one of its “doctrines” namely the validity of mediators who are entitled to mediate in divorce disputes are mediators consisting of judges or non-judge but certified mediators. This has implications for the "oppression" of local mediators with a wealth of functional insight into the life of village communities. For this reason, in this mentoring program, we use Asset Based Community Development (ABCD) as the approach used. This departs from the initial assumption that local mediators have the ability and insight that are functional in people's lives, primarily related to divorce dispute resolution. Through this mentoring program, there is an increase in the understanding of mediators in understanding and practicing mediation which is known outside the provisions of fiqh, as a companion to the abilities they already have.